Sustaining Open And Distance Learning (ODL) in statistical learning during and post pandemic covid-19 / Nor Faezah Mohamad Razi ... [et al.] - Mohamad Razi, Nor Faezah; Baharun, Norhayati; Sarkam, Nor Aslily; Mohammad, Nor Hazlina (2020)
Despite the Covid pandemic era, various sectors have changed in terms of administration as well as operations. Teaching and learning methods have changed from a traditional didactic approach to new delivery methods to deal with the effects of this pandemic and it is believed to be effective. It is an effort that has been made to comply with the Standard Operating Procedure (SOP) of social imprisonment. It is seen in line with Education 5.0 defined learning as a centric ecosystem that is sustainable, balanced, and conscientious, driven by values, powered by the intellect, and afforded by new, ubiquitous technologies. A major concern appears on the level of the student's ability to proficiently. Many students are not ready to participate in online classes, especially in the course that required calculation, particularly the Probability and Statistics course. Thus, an instrument consists of 20 items was developed by an experienced lecturer to measure the level of student's ability between the two groups. Data were captured through an interactive e-learning platform and analyzed using Rasch measurement method. Hence this study aims to explore students' understanding of counting rule and its probability concepts and examine which ideas were found most difficult by the students to understand.